Dinamika Sekolah dalam Meningkatkan Karakter Kedisiplinan Siswa UPT SMPN 2 Galesong Selatan - Rahma Dani; Irma Suryani Arfah; Abdul Wahid (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Discipline is a fundamental characteristic that supports student learning success. However, at the UPT SMPN 2 Galesong Selatan, high rates of lateness and irregular student behavior are still found, so an in-depth study of the school's role in fostering such discipline is needed. This study aims to understand school dynamics, identify supporting and inhibiting factors, and formulate effective strategies for improving disciplined behavior. Using qualitative methods and an interpretive phenomenological approach, data were obtained through interviews, 14 days of observation, and documentation review. Then, they were analyzed using the Miles, Huberman, and Saldaña model. The research findings indicate that coordination between the principal, vice principal for student affairs, guidance counselor, and student council president has a significant contribution to fostering student discipline. The micro-skills-based counseling program and the “Discipline Challenge” activity initiated by the student council have proven effective in increasing student compliance. The main obstacles that still arise include low parental involvement and increased teacher fatigue during the final lesson period. Based on these results, the study concluded that the implementation of teacher rotation on duty, the use of digital behavioral contracts, and strengthening the role of the Student Council (OSIS) are relevant and sustainable strategies in efforts to improve student discipline.